Tailoring Spectral and Photochemical Properties of Bioinspired Retinal Mimics by in Silico Engineering. (15th September 2020) - El‐Tahawy, Mohsen M. T.; Conti, Irene; Bonfanti, Matteo; Nenov, Artur; Garavelli, Marco
Abstract: Controlling the spectral tunability and isomerization activity is currently one of the hot topics in the design of photoreversible molecular switches for application in optoelectronic devices. The present work demonstrates how to manipulate the absorption of the retinal protonated Schiff base (rPSB) chromophore over the entire visible range by targeted functionalization of the retinal backbone. Moreover, a correlation between the vertical excitation energy and the profile of the potential energy surface of the bright excited state responsible for the photoreactivity of rPSB is established. This correlation was exploited to rank the functionalized rPSBs into different classes with characteristic photoisomerization activity. Eventually, the synergic effects of functionalization and of external electric fields in the range of a few MV cm −1 were applied to achieve reversable and regioselective control of the photoisomerization propensity of selected rPBS derivatives. Abstract : The absorption of the retinal protonated Schiff base (rPSB) chromophore is manipulated over visible range by targeted functionalization of the retinal backbone. A correlation between the vertical excitation energy and the profile of the potential energy surface of the bright excited state is established. The synergic effects of functionalization and of external electric fields achieve reversable and regioselective control of the photoisomerization propensities of select rPBS derivatives.